Instagram vs. Facebook: A Quasi Experimental Study on Expository Writing Outcomes among Grade X Students (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
The increasing integration of technology in education necessitates innovative learning strategies, especially in language instruction. This study investigates the comparative effectiveness of Instagram and Facebook as digital learning media for expository writing instruction among Grade X students at SMA Negeri 7 Bulukumba. The research addresses the gap in existing literature, which has seldom compared social media platforms simultaneously in genre-specific writing contexts. Employing a quantitative approach with a quasi-experimental nonequivalent control group design, the study involved 54 students divided into two groups: one using Instagram and the other using Facebook as learning media. Pretest and posttest assessments were conducted to evaluate students' expository writing skills across five dimensions: content, structure, coherence, rules, and grammar. The results revealed a statistically significant improvement in the Instagram group, whose average score increased from 52.04 to 70.70, compared to the Facebook group, which only rose from 46.85 to 50.96. The findings underscore Instagram’s superior affordances—its emphasis on visual content, comment interaction, hashtag organization, and story features—supporting multimodal learning and peer feedback mechanisms. These affordances promote deeper engagement, collaborative learning, and alignment with students' digital habits, thereby enhancing motivation and skill development. In contrast, Facebook’s chronological and text-dominant interface yielded minimal impact. The study concludes that Instagram is more effective than Facebook for enhancing students’ expository writing outcomes and recommends its strategic integration in language curricula. Teachers should be trained in using Instagram’s pedagogical features, and policymakers should consider its inclusion in national digital literacy strategies. These findings align with the Merdeka Curriculum's emphasis on contextual, student-centered learning, and suggest that effective social media use can bridge formal education with students’ everyday digital experiences, paving the way for broader curriculum reforms that embrace relevant, engaging, and technology-enhanced instruction.